2015
DOI: 10.1007/s00221-015-4233-9
|View full text |Cite
|
Sign up to set email alerts
|

(Dis-)Harmony in movement: effects of musical dissonance on movement timing and form

Abstract: While the origins of consonance and dissonance in terms of acoustics, psychoacoustics and physiology have been debated for centuries, their plausible effects on movement synchronization have largely been ignored. The present study aimed to address this by investigating whether, and if so how, consonant/dissonant pitch intervals affect the spatiotemporal properties of regular reciprocal aiming movements. We compared movements synchronized either to consonant or to dissonant sounds and showed that they were diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…Moreover, it can be seen how listening to different kinds of music during exercise can have an effect on both affective states and motor performance in physical activity [14,15]. People have shown an implicit ability to synchronise their movements with music [29] and that certain music can even motivate more exercise/limit the effects of exertion [14,15]. From this work, it can be seen how powerful a tool musical sound can be in promoting physical activity.…”
Section: Musical Expectancy and Movementmentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, it can be seen how listening to different kinds of music during exercise can have an effect on both affective states and motor performance in physical activity [14,15]. People have shown an implicit ability to synchronise their movements with music [29] and that certain music can even motivate more exercise/limit the effects of exertion [14,15]. From this work, it can be seen how powerful a tool musical sound can be in promoting physical activity.…”
Section: Musical Expectancy and Movementmentioning
confidence: 92%
“…This musical expectancy has been demonstrated to impact people's movement. The work by Komeilipoor et.al [29] showed how musical dissonance impacts people ability to synchronise their movement with an external musical stimulus. It was found that participants were able to better synchronise with a consonant sound (one that fits expectation) than a dissonant sound (one which defies such expectations).…”
Section: Musical Expectancy and Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have suggested before, exposure to harmonic music might be at the base of processing advantages for consonance (Komeilipoor et al, 2015;Schellenberg & Trehub, 1994, 1996. Preference for acoustic stimuli defined by simple frequency ratios between their composing tones could be a prerequisite to benefit from differences between consonance and dissonance as has been observed in human participants (Crespo-Bojorque & Toro, 2016).…”
Section: Experience and The Emergence Of Consonance Preferencesmentioning
confidence: 72%
“…In contrast, rats showed no differences across experiments. Their differences between consonant and dissonant chords have also been identified in both human adults (Komeilipoor, Rodger, Craig, & Cesari, 2015;Schellenberg & Trehub, 1994) and infants (Schellenberg & Trehub, 1996). Consonant chords and melodies seem to be better processed than dissonant ones.…”
Section: Processing Advantagesmentioning
confidence: 76%